2018
DOI: 10.18311/jbc/2017/16285
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of release rate of Trichogramma chilonis (Ishii) in bio-intensive management of Chilo partellus (Swinhoe) in fodder maize

Abstract: The early season attack of Chilo partellus, in kharif sown fodder maize inflicts appreciable losses, if unchecked. Biointensive management with the use of egg parasitoid Trichogramma chilonis Ishii in fodder maize through different doses and release rate was standardized. The results of the trials from two years showed that damage parameters like Leaf Injury (LI), recorded three weeks after parasitoid release from 0.25-6.00 per cent across different treatments whereas in untreated control it was 6.50-13.25 %, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…not only reduced the pest infestation in maize but also yielded insecticide free quality produce. The study finds support from Kumar and Kanta (2011) who reported significantly lower damage caused by the maize stem borer in the plots wherein T. chilonis was released @ 100 000 per ha on 12 and 15 day old maize crop and subsequently it increased the grain yield. Jalali and Singh (2003) studied the parasitization efficiency of four Trichogramma species, viz.…”
supporting
confidence: 68%
“…not only reduced the pest infestation in maize but also yielded insecticide free quality produce. The study finds support from Kumar and Kanta (2011) who reported significantly lower damage caused by the maize stem borer in the plots wherein T. chilonis was released @ 100 000 per ha on 12 and 15 day old maize crop and subsequently it increased the grain yield. Jalali and Singh (2003) studied the parasitization efficiency of four Trichogramma species, viz.…”
supporting
confidence: 68%
“…Likewise, these findings are also supported by Ahmed et al (2002) who reported that spinosad was effective to reduce infestation from 10.7% before sprays to 3.1% seven day after first spray and to 0.7% at seven day of second spray. Kumar and Kanta (2011) who reported significantly lower damage caused by the maize stem borer and subsequently increased the grain yield in the plots with where in T. chilonis was released @ 100000 eggs ha -1 on 12 with 4.41% in dead heart was recorded followed by nimbicidine (5.43 %) as the least effective among the treatments but was significantly superior to untreated control (10.18%) in combined analysis. These findings are in conformity with the findings of Choudhary et al (2017) who found nimbicidine @ 5 mL L -1 of water with 5.13 percent dead heart.…”
Section: Foliar Damage and Dead Heart Percentagementioning
confidence: 88%
“…It has become a serious threat in maize and sorghum based cropping systems not only in India and Asia but also throughout the world (Sylvain et al, 2015). It has attained the status of key pest causing 18 to 25% yield losses in maize and has also been reported feeding on paddy, sugarcane and other millets (Harris, 1990;Kumar and Kanta, 2011). Due to internal nature of damage, this pest is very difficult to control by conventional insecticides.…”
mentioning
confidence: 99%